Local Wisdom Themes in Project for Strengthening the Profile of the Pancasila Student: A New Perspective on Science Learning in Junior High School - Arti, Yuli; Widowati, Asri (Universitas Negeri Yogyakarta, 2025)
The research aimed to analyze science learning through the implementation of the Project for Strengthening the Profile of Pancasila Student (P5) with local wisdom theme in Junior High School (SMP). The focus of the study was to explore the methods, employed within the Project for Strengthening the Profile of Pancasila Student framework. Also, it aimed to analyze the science learning processes during these activities, particularly in relation to local wisdom themes. Data were collected from 97 students in grades VII, VIII, and IX at SMP PIRI 1 Yogyakarta through observations on November 28, 2023, and simple interviews with students and teachers to collect feedback on the Project for Strengthening the Profile of Pancasila Student activities. The local wisdom theme was